Rapid detection of Mycobacterium avium in stool samples from AIDS patients by immunomagnetic PCR. - Li, Z (1996)
Direct PCR detection of bacteria in clinical samples is often hindered by the presence of compounds that inhibit the PCR. To improve and accelerate the diagnosis of Mycobacterium avium-M. intracellulare complex infections, an immunomagnetic PCR (IM-PCR) assay was developed. This IM-PCR procedure combines the separation of mycobacteria by antimycobacterial monoclonal antibody coupled to magnetic beads with an M. avium-M. intracellulare complex-specific PCR protocol based on 16S rRNA gene sequences. As few as 10 M. avium bacilli were detected in spiked human stool samples, a clinical specimen usually refractory to conventional PCR analysis, by the IM-PCR method. Moreover, M. avium organisms were detected in about 24 h in 18 of 22 culture-confirmed fecal samples from AIDS patients. This IM-PCR protocol should allow for the rapid and sensitive detection of M. avium isolates in clinical specimens.